Cybersecurity for Small and Medium-Sized Businesses - Luukkonen, Oliver A.; Sönmez, Yeşim Ülgen (İstanbul Gelişim Üniversitesi, 2022)
Cybersecurity is all the devices and software applications that protect computers, networks, software, critical systems, and data from possible digital threats. The organizations have a responsibility to secure data to maintain customer trust and ensure regulatory compliance. They use cybersecurity measures and tools to protect sensitive data from unauthorized access, as well as prevent disruption to business operations due to unwanted network activity, and implement cybersecurity by streamlining digital defense across employees, processes, and technologies. Small and medium-sized businesses (SMBs) which make up a large portion of organizations, contribute greatly to the economies of many countries. However, SMBs tend to not care enough about cyber security or do not have the resources to implement it. Additionally, cybersecurity research rarely focuses on SMBs. SMBs have extensively switched to remote/hybrid working due to the global pandemic COVID-19 and this transition to remote/hybrid working methods had to adopt new digital strategies and technologies very quickly. This situation has led to the emergence of more cyber risks and cyber-attacks. This study highlights that it is crucial to strengthen SMBs and future preparedness against cybersecurity threats. Specifically, in this study, cyber security problems and deficiencies in SMBs are identified and suggestions are offered to eliminate them. Also, the work has shown the importance of why the countries should give importance to SMB cybersecurity as well as the defense industry and future studies should focus more on SMB cybersecurity applications.
Keywords: Business Administration; İşletme; Business Systems in Context (Other); İş Sistemleri (Diğer)